Correlations between Obesity, Polycystic Ovary Syndrome, and Sleep Apnea: A Meta-Analysis - Jayanti, Saktryana Endang Ragil; Widyaningsih, Vitri; Budihastuti, Uki Retno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Obesity is one of the biggest public health problems in the world. Obesity is associated with various health problems, decreased quality of life and death. Obesity is known to have an impact on women's lives, namely Polycystic Ovary Syndrome (PCOS) which if not treated immediately can cause sleep apnea. This study aims to analyze the relationship between obesity and PCOS and sleep apnea. Subjects and Method: This research is a systematic review and meta-analysis. Population = women, Intervention = obesity, Comparison = not obese, Outcomes = PCOS and sleep apnea. Article searches through journal databases include: PubMed, Science Direct, Google Scholar, and Springerlink. The keywords used are obesity OR obese AND PCOS OR “Polycystic Ovary Syn- drome” AND “sleep apnea” OR “Poor Sleep” OR “obstructive sleep apnea”. Articles were selected with the help of PRISMA flow diagrams. Inclusion criteria include full-text articles with obser- vational studies, multivariate analysis results in the form of aOR values and published from 2012- 2021. Eligible articles were analyzed using the Revman 5.3 application. Results: Eighteen articles from the United States, Brazil, China, Turkey, Iraq, Pakistan, Sri Lanka, Korea, West Africa, East Africa, Nigeria and the United Kingdom were included in the meta- analysis. A meta-analysis of the results of the case-control study design subgroup (4 articles) and the cross-sectional study (4 articles) showed that obese women had a 1.14-fold increased risk of developing PCOS compared to non-obese women (aOR = 1.14; 95% CI = 1.03 to 1.26; p= 0.010). A meta-analysis of 10 cross-sectional studies showed that obese women increased the risk of developing sleep apnea 4.66 times than non-obese women (aOR = 4.66; 95% CI = 3.23 to 6.71; p = <0.001). Conclusion: Obesity is a risk factor for PCOS (Polycystic Ovary Syndrome) and sleep apnea in women. Keywords: obesity, PCOS, sleep apnea, meta-analysis. Correspondence: Saktryana Endang Ragil Jayanti. Master’s Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: Saktryana.agil@gmail.com. Mobile: 082242154117.